2013
DOI: 10.1016/j.amepre.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Nicotine Delivery Systems

Abstract: Background Electronic nicotine delivery systems (ENDS) initially emerged in 2003 and have since become widely available globally, particularly over the Internet. Purpose Data on ENDS usage patterns are limited. The current paper examines patterns of ENDS awareness, use, and product-associated beliefs among current and former smokers in four countries. Methods Data come from Wave 8 of the International Tobacco Control Four-Country Survey, collected July 2010 to June 2011 and analyzed through June 2012. Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
338
10
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 571 publications
(388 citation statements)
references
References 19 publications
31
338
10
9
Order By: Relevance
“…Shiffman, Pillitteri, Burton, and Di Marino (2004) did show that simulated ads describing Eclipse reduced intentions to quit among smokers, and Hughes, Keely, and Callas (2005) showed that Eclipse users were no more or less likely to have quit at 6 months follow-up compared with other smokers. More recently, several studies have evaluated the use of e-cigarettes by cigarette smokers, which indicate that smokers report using them to help quit or cut down on smoking (Adkison et al, 2013;Etter, 2010;Etter & Bullen, 2011;Pearson, Richardson, Niaura, Vallone, & Abrams, 2012;Pokhrel, Fagan, Little, Kawamoto, & Herzog, 2013;Regan, Promoff, Dube, & Arrazola, 2013;Vickerman, Carpenter, Altman, Nash, & Zbikowski, 2013). None of the unconventional tobacco products evaluated in this study have been approved as smoking cessation aids.…”
Section: Introductionmentioning
confidence: 99%
“…Shiffman, Pillitteri, Burton, and Di Marino (2004) did show that simulated ads describing Eclipse reduced intentions to quit among smokers, and Hughes, Keely, and Callas (2005) showed that Eclipse users were no more or less likely to have quit at 6 months follow-up compared with other smokers. More recently, several studies have evaluated the use of e-cigarettes by cigarette smokers, which indicate that smokers report using them to help quit or cut down on smoking (Adkison et al, 2013;Etter, 2010;Etter & Bullen, 2011;Pearson, Richardson, Niaura, Vallone, & Abrams, 2012;Pokhrel, Fagan, Little, Kawamoto, & Herzog, 2013;Regan, Promoff, Dube, & Arrazola, 2013;Vickerman, Carpenter, Altman, Nash, & Zbikowski, 2013). None of the unconventional tobacco products evaluated in this study have been approved as smoking cessation aids.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the quality of the evidence in support of e-cigarettes' effectiveness in helping smokers quit, according to the GRADE system, was again assessed as very low to low (Malas et al, 2016). Considering only studies with a moderate or strong quality score (Malas et al, 2016), 10 studies other than RCTs examined the relationship between e-cigarette use and smoking status in the real world by surveying regular e-cigarette users Goniewicz et al, 2013;Dawkins et al, 2013;Polosa et al, 2014;Adriaens et al, 2014;Adkison et al, 2013;Christensen et al, 2014;Brown et al, 2014;Biener and Hargraves, 2015). Samples in 5 studies were not representative, and results have to be interpreted with caution Lechner et al, 2015;Goniewicz et al, 2013;Dawkins et al, 2013;Polosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Although e-cigarette awareness and use are increasing in Canada, there have been few attempts to describe e-cigarette users. 9,12,20,21 An online survey of 1188 young adults found that 43% were aware of e-cigarettes and 5.7% were current e-cigarette users. 12 This same study also revealed that 80% of current cigarette smokers reported an interest in trying e-cigarettes to help them quit smoking or to use in places where smoking is banned.…”
Section: Introductionmentioning
confidence: 99%